Impact of COVID-19 vaccination program on seroprevalence in blood donors in England, 2021. Issue 2 (August 2021) - Whitaker, Heather J; Elgohari, Suzanne; Rowe, Cathy; Otter, Ashley David; Brooks, Tim; Linley, Ezra; Hayden, Iain; Ribeiro, Sonia; Hewson, Jacqueline; Lakhani, Anissa; Clarke, Eleanor; Tsang, Camille; et al.
Highlights: An estimated 93.5% of 70 to 84-year-old blood donors had antibodies against COVID-19 from late February 2021. Only around 5% of 70 to 84-year old donors had antibodies from natural infection, which suggests the vaccine is producing a good immune response in older people following a single vaccine dose. Prevalence of antibodies from natural infection have remained stable in older donors since late December 2020, suggestive of vaccine impact. Summary: The COVID-19 vaccination programme commenced in England on 8th December 2020 primarily based on age; by 7th March 2021 approximately 93% of the English population aged 70+ years had received at least 1 dose of either the Pfizer BioNTech or AstraZeneca vaccines. Using a nucleoprotein assay that detects antibodies following natural infection only and a spike assay that detects infection and vaccine-induced responses, we aim to describe the impact of vaccination on SARS-CoV-2 antibody prevalence in English blood donors.